Nurses’ Awareness on Patient Safety Culture in A Newly Established University Hospital - Mohd Said Nurumal; Najwatul Madihah Sabran; Siti Hazariah Abdul Hamid; Muhammad Kamil Che Hasan (Jurnal Keperawatan Indonesia, 2020)
As a vital part of patient care delivery, patient safety culture contributes to the quality of care provided by nurses. Safe patient care is positively linked to the attitudes of nurses. This study aimed to assess the perception of nurses working in a newly established teaching hospital. A cross-sectional study involving 194 nurses from three different units was conducted by using a 24-item Hospital Survey of Patient Safety Culture. Data on gender, working unit, age, years of working, and attendance in workshops on patient safety were also collected. The majority of the nurses had a positive total score of patient safety culture. The lowest score was 76 (63%), and the highest score was 120 (96%). The awareness on patient safety culture significantly differed between gender, years of working, and working units. Post-hoc comparisons using Tukey’s HSD test yielded a significant difference between nurses from critical care units and those from medical and surgical units. The mean score and total positive score on awareness on patient safety culture of the former were higher than those of the latter. Overall, the majority of the staff nurses in International Islamic University Malaysia Medical Center had a positive total score on awareness on patient safety culture. Awareness on patient safety, which is considered crucial worldwide, should be enhanced to influence the development of a positive patient safety culture within hospitals. This implementation would directly develop high-quality care to patients and positively impact health organizations. Abstrak Kesadaran Perawat terhadap Budaya Keselamatan Pasien di Rumah Sakit Universitas yang Baru Dibangun. Sebagai bagian penting dari pemberian perawatan pasien, budaya keselamatan pasien berkontribusi pada kualitas perawatan yang diberikan oleh perawat. Perawatan pasien yang aman secara positif terkait dengan sikap perawat. Penelitian ini bertujuan untuk menilai persepsi perawat yang bekerja di rumah sakit pendidikan yang baru dibangun. Sebuah studi cross-sectional yang melibatkan 194 perawat dari tiga unit yang berbeda dilakukan dengan menggunakan Survei Rumah Sakit Budaya Keselamatan Pasien. Data tentang jenis kelamin, unit kerja, usia, tahun kerja, dan kehadiran dalam lokakarya tentang keselamatan pasien juga dikumpulkan. Mayoritas perawat memiliki skor total positif dari budaya keselamatan pasien. Skor terendah adalah 76 (63%), dan skor tertinggi adalah 120 (96%). Kesadaran tentang budaya keselamatan pasien berbeda secara signifikan antara jenis kelamin, tahun kerja, dan unit kerja. Perbandingan post-hoc menggunakan uji HSD Tukey menghasilkan perbedaan yang signifikan antara perawat dari unit perawatan kritis dan mereka dari unit medis dan bedah. Skor rata-rata dan skor total positif pada kesadaran tentang budaya keselamatan pasien dari yang pertama lebih tinggi daripada yang terakhir. Secara keseluruhan, mayoritas staf perawat di International Islamic University Malaysia Medical Center memiliki skor total positif pada kesadaran tentang budaya keselamatan pasien. Kesadaran akan keselamatan pasien, yang dianggap penting di seluruh dunia, harus ditingkatkan untuk memengaruhi perkembangan budaya keselamatan pasien yang positif di rumah sakit. Implementasi ini secara langsung akan mengembangkan perawatan berkualitas tinggi kepada pasien dan berdampak positif bagi organisasi kesehatan. Kata Kunci: budaya, keselamatan pasien, perawat, rumah sakit